Developing a New qFIBS Model Assessing Histological Features in Pediatric Patients With Non-alcoholic Steatohepatitis - Liu, Feng; Wei, Lai; Leow, Wei Qiang; Liu, Shu-Hong; Ren, Ya-Yun; Wang, Xiao-Xiao; Li, Xiao-He; Rao, Hui-Ying; Huang, Rui; Wu, Nan; Wee, Aileen; Zhao, Jing-Min (Frontiers in Medicine, 2022)
Background: The progression of nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis (NASH) in children is associated with unique histological features. Histological assessment of liver tissue is often hampered by interobserver variability and diagnostic consensus is not always achieved. We investigated whether the qFIBS technique derived from adult NASH could be applied to pediatric NASH. Materials and Methods: 102 pediatric patients (<18 years old) with biopsy-proven NASH were included. The liver biopsies were serially sectioned for hematoxylin-eosin and Masson trichrome staining for histological scoring, and for second harmonic generation (SHG) imaging. Using the NASH CRN scoring system as the reference standard, qFIBS-automated measures of fibrosis, inflammation, hepatocyte ballooning and steatosis were developed Results: qFIBS showed the best correlation with steatosis (r=0.84, P<0.001); with ability to distinguish different grades of steatosis (AUROCs 0.90 and 0.98, sensitivity 0.71 and 0.93, and specificity 0.90 and 0.90). qFIBS correlation with fibrosis (r=0.72, P<0.001) was good with high AUROC values [qFibrosis (AUC) >0.85 (0.85-0.95)] and ability to distinguish different stages of fibrosis. qFIBS showed weak correlation with ballooning (r=0.38, P=0.028) and inflammation (r=0.46, P=0.005); however, it could distinguish different grades of ballooning (AUROCs 0.73, sensitivity 0.36 and specificity 0.92) and inflammation (AUROCs 0.77, sensitivity 0.83 and specificity 0.53). Conclusion: It was demonstrated that when qFIBS derived from adult NASH was performed on pediatric NASH, it could best distinguish the various histological grades of steatosis and fibrosis.